2016
DOI: 10.5565/rev/jtl3.669
|View full text |Cite
|
Sign up to set email alerts
|

Conversación en WhatsApp: aprendizaje y colaboración en lingua franca

Abstract: Resumen En este estudio de caso se analiza una conversación de WhatsApp (WA) entre dos estudiantes, inscritas en una misma asignatura universitaria, quienes utilizan el inglés como lengua franca. Con la intención de observar el establecimiento de los roles en un trabajo colaborativo mediado por Mobile Instant Messaging (MIM), se abordan los datos desde una perspectiva socioconstructivista, y se emplea el Análisis Conversacional (AC) para describir cómo se posicionan las dos estudiantes con competencias desigua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 13 publications
0
1
0
2
Order By: Relevance
“…As previously mentioned, the role is a social construction that emerges in the interaction and defines the behaviour of the actors (Goffman, 1959, in Gómez, Shafirova, 2016. The interaction is then the place or moment in which the roles are defined.…”
Section: Role Assignmentmentioning
confidence: 99%
“…As previously mentioned, the role is a social construction that emerges in the interaction and defines the behaviour of the actors (Goffman, 1959, in Gómez, Shafirova, 2016. The interaction is then the place or moment in which the roles are defined.…”
Section: Role Assignmentmentioning
confidence: 99%
“…Ali (2017) también indica que esta red social, desde la perspectiva de los teléfonos inteligentes, permite conectar con los compañeros y aprender de forma colaborativa en cualquier momento. Así también, Gómez y Shafirova (2016), Comas-Quinn, De los Arcos y Mardomingo (2012) y Palacios (2020) confirman que WhatsApp favorece el aprendizaje colaborativo, así como diferentes formas de interacción y participación social, además de que se pueden establecer distintos roles entre los participantes de un grupo (Gómez y Shafirova, 2016).…”
Section: Trabajo En Equipo (19%)unclassified
“…Following Vygotsky (1962), social interaction plays an essential role in learning and CMC tasks may, therefore, be a useful activity for building knowledge. Gómez and Shafirova (2016), after analysing a collaborative learning task using MIM, concluded that cooperation is a fundamental element in the learning process, as acquiring knowledge is never an isolated undertaking, but a social enterprise.…”
Section: Cmc In Fl Teaching and Learningmentioning
confidence: 99%